DETERMINANTS OF FUNDAMENTAL STOCK RETURN FACTORS AT TEXTILE AND GARMENT COMPANY, ANALYSIS DATA PANEL FOR PERIOD 2012 - 2019 - Sihombing, P. Sihombing; Fanny Ferdiantoputera Sinaga (Dinasti Publisher, 2020)
This research aims to examine and analyze the effect of current ratio, total asset turnover, debt to equity ratio and return on equity on the value of stock of textile and garment companies in the Indonesia Stock Exchange for the period of 2012 to 2019. This research uses annual data for the observation period from 2012 to 2019. The population is textile and garment companies listed on the Indonesia Stock Exchange in 2012 to 2019 and up to 19 companies. The sampling technique used purposive sampling, found a sample of 7 companies with 8 years observation so that the total observation obtained was 56. The model used is the Common Effect Model. The results of the analysis show that the total asset turnover have a significant negative effect and return on equity have a significant positive effect, while the current ratio and debt to equity ratio have no significant effect on stock returns of textile and garment companies in the Indonesia Stock Exchange for the period of 2012 to 2019.